Rediscovery of the holotype of Characidium sanctjohanni Dahl 1960 (Characiformes: Crenuchidae) from the Colombian Pacific slope - Agudelo-Zamora, Henry D.; Ortega-Lara, Armando; Taphorn B., Donald C. (Papéis Avulsos de Zoologia, 2014)
We report the rediscovery of the holotype of Characidium sanctjohanni Dahl, previously considered as lost in the ICN collections. We present counts, measurements and photographs, also offering a comparison between the holotype and the original description.